Pengaruh Keterampilan Kewirausahaan Dan Saluran Distribusi Terhadap Minat Beli Susu Kambing Etawa Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2021 - Sujarwo, Revi Moury Putri; Salim, Muhammad Agus; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study was to determine and analyze the influence of entrepreneurial skills and distribution channels simultaneously on the interest in buying Etawa goat's milk among students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2021. The population in the study were students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2021 who had an interest in buying Etawa goat's milk whose number was not known for certain. The approach method used a non-probability sampling technique, namely purposive sampling, which is a sample collection technique based on certain criteria using a questionnaire distributed to 72 respondents and using the SPSS analysis tool. The results of the study showed that entrepreneurial skills and distribution channels simultaneously influenced the interest in buying Etawa goat's milk among students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2021. Partially, entrepreneurial skills and distribution channels influenced the interest in buying Etawa goat's milk among students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2021. Keywords: Entrepreneurial Skills, Distribution Channels, And Buying Interest